Adapted karate training on functional autonomy, muscle strength and quality of life of elderly man with osteoporosis: a clinical case - Borba-Pinheiro, Claudio Joaquim; Martin Dantas, Estelio Henrique; Jesus, Fernando Pereira de; Barreto Rocha-Junior, Olavo Raimundo; Drigo, Alexandre Janotta; Gurgel de Alencar Carvalho, Mauro Cesar; Almeida de Figueiredo, Nebia Maria (Archives Budo Science Martial Arts & Extreme Sports, 2016)
Background & Study Aim: With advancing age, the decrease of functional capabilities, increasing the occurrence of diseases, among them, osteoporosis that is characterized by loss of bone mineral density, making bones fragile and susceptible to fractures. Aim of the study was the effect of adapted karate training (AKT) in functional autonomy, muscle strength and quality of life (QoL) of elderly man with osteoporosis. Materials & Methods: An elderly man of ethnic Euro-American South with 75 yrs. of age with osteoporosis participated in the study. The program AKT had a three-month period with frequency 3 x wk. in alternate days and with 60 min/class. The functional autonomy by Latin American Maturity Development Group Protocol: 10-m walk (10MW), rising from sitting position (RSP), rising from ventral decubitus position (RVDP) among other tests; the strength of the lower limbs by 10 repetitions maximum (10RM) test in 45 degrees leg press and leg extension, the short form 36 (SF-36) for assessment of QoL and osteoporosis was determined by Absorptiometry Dual energy X-ray were evaluated. Results: There was an increase for physical health Delta% = 10%, mental health Delta% = 4% and total QoL Delta% = 5.5%. To functional autonomy increases were observed for all tests, including: RVDP Delta% = -9.18%, RSP Delta% = -22.92%, C10mw Delta% = -21.45. In addition, showed increases in the leg press 45 degrees Delta% = 16.05% and knee extension Delta% = 15.15% tests. Conclusions: For case study, assessments performance and health variables showed increases in functional autonomy, strength and QoL of elderly men with osteoporosis after AKT. Therefore, it is an empirical justification for the need to intensify research in order to verify the suitability of martial arts in the treatment of osteoporosis.
Keywords: bone mineral density; combat sport; martial arts; physical inactivity; resistance training